La sugerencia.
De $$\sum{cyc}\left(\frac{x^2}{y}-2x+y\right) \geq \sum{cyc}\left(\frac{(y+z)^2}{z+x}-2(y+z)+(z+x)\right)$ $ o $$\sum{cyc}\frac{(x-y)^2}{y}\geq\sum{cyc}\frac{(x-y)^2}{z+x}$ $ o $$\sum_{cyc}(x-y)^2S_z\geq0,$ $ donde $S_z=\frac{1}{y}-\frac{1}{z+x}.$
Ahora, por C-S $$\sum_{cyc}Sx=\sum{cyc}\left(\frac{1}{x}-\frac{1}{x+y}\right)=\sum{cyc}\left(\frac{1}{2}\left(\frac{1}{x}+\frac{1}{y}\right)-\frac{1}{x+y}\right)\geq$ $ $$\geq\sum{cyc}\left(\frac{1}{2}\cdot\frac{4}{x+y}-\frac{1}{x+y}\right)=\sum{cyc}\frac{1}{x+y}>0$ $ y #% $ $$\sum{cyc}S_xSy=\sum{cyc}\left(\frac{1}{z}-\frac{1}{x+y}\right)\left(\frac{1}{x}-\frac{1}{y+z}\right)=$ $ $$=\sum{cyc}\left(\frac{1}{xy}-\frac{1}{z(y+z)}-\frac{1}{x(x+y)}+\frac{1}{(x+y)(x+z)}\right)=$ $ $$=\sum{cyc}\left(\frac{1}{xy}-\frac{1}{y(x+y)}-\frac{1}{x(x+y)}+\frac{1}{(x+y)(x+z)}\right)=$la $$=\sum_{cyc}\frac{1}{(x+y)(x+z)}>0.$$
Ahora, desde el $$\sum_{cyc}S_x>0,$$ we can assume that $ S_y + S_z > 0$.
Además, contamos con $$\sum_{cyc}(x-y)^2S_z=(x-y)^2S_z+(x-y+y-z)^2S_y+(y-z)^2S_x=$ $ $$(S_y+S_z)(x-y)^2+2(x-y)(y-z)S_y+(S_x+S_y)(y-z)^2$ $ y es suficiente para probar $$S_y^2-(S_z+S_y)(S_x+Sy)\leq0,$ $ $\sum\limits{cyc}S_xS_y\geq0$.
¡Hecho!